2002
DOI: 10.1074/jbc.m203607200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein Expression at the Stage of Neural Tube Closure in the Mouse Embryo

Abstract: Analysis of the protein complement of a biological system through proteomics provides the opportunity to directly monitor the functional readout of gene expression. In this study, proteomics was applied to the mouse embryo to investigate the molecular events underlying the processes occurring at the stage of neural tube closure. Protein profiles of embryos between embryonic days 8.5 and 10.5 exhibited a number of stage-specific changes. Identification of developmentally regulated proteins by mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…Still we found that the correlation between mRNA and protein expression changes was very low in our study on the level of individual proteins and did not exceed 30%, although 88% of the differentially expressed proteins were represented by mRNAs. This is consistent with previous studies in which mRNA data did not necessarily correlate well with protein data (72)(73)(74)(75)(76), although these studies did not investigate changes due to disease. In a recent study using brain cortex tissue, we found a 60 -70% overlap between mRNA and protein changes during embryonic development where processes are highly predetermined and may be regulated to a large degree by mRNA expression with subsequent protein changes (35).…”
Section: Overlap Of Protein Expression Changes Between Different Stagsupporting
confidence: 82%
“…Still we found that the correlation between mRNA and protein expression changes was very low in our study on the level of individual proteins and did not exceed 30%, although 88% of the differentially expressed proteins were represented by mRNAs. This is consistent with previous studies in which mRNA data did not necessarily correlate well with protein data (72)(73)(74)(75)(76), although these studies did not investigate changes due to disease. In a recent study using brain cortex tissue, we found a 60 -70% overlap between mRNA and protein changes during embryonic development where processes are highly predetermined and may be regulated to a large degree by mRNA expression with subsequent protein changes (35).…”
Section: Overlap Of Protein Expression Changes Between Different Stagsupporting
confidence: 82%
“…This translocates from the cytosol to the nucleus in response to oxidative stress (37). The mouse PICOT homologue is differentially expressed at stages of mouse embryogenesis concomitant with neural tube closure (38).…”
mentioning
confidence: 99%
“…N-Copine has been reported to be associated with OS-9, a protein that is frequently over-expressed in osteosarcoma [13]. N-Copine has also been implicated in synaptic plasticity and development [12,14]. While Copines are calcium-dependent phospholipid-binding proteins with intrinsic kinase activity [7][8][9], their physiological function in mammals is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Copine 8 is strongly expressed in the prostate, brain, and heart tissues but is also detected in most other tissues examined at low levels. Copines are highly conserved across species and it is possible that the family members may play a pivotal role in development and mitogenesis [12,13]. Copine 8 has the strongest homology to N-Copine with $60% homology at the protein level.…”
Section: Discussionmentioning
confidence: 99%